The trade name and its use by the legal entity - Pazos Hayashida, Javier Mihail (2015)
This article analyzes the trade name function as a distinctive sign of the economic agents, and the use of it, having in consideration the problems with the confusion between legal entity name, label or business sign, and service mark. Furthermore, it discusses the origin of the exclusive right to a trade name, the proof of its use, and the effects when use of the sign ceases.